Optimizing the Enforcement of Traffic Violations Through the Precision National Mobile ETLE Application by the Klaten Police Traffic Unit to Realize Equitable Law Enforcement - Rahmadi, Farrel Jodi (Advances in Police Science Research Journal, 2024)
Law Enforcement aims to regulate life and order in society. There are 3 elements of law that must be considered, namely Justice, Benefit, and Certainty. The law must be enforced fairly. Law enforcement is a solution to world problems. The problem of road safety, namely the high number of traffic accidents, has become a world issue, various plans at the global level through the United Nations, the ASEAN level and Indonesia, all move in order to reduce the number of traffic accidents with an emphasis on one of them, namely law enforcement. One of the Chief of Police’s emphases is the development of ETLE-based traffic law enforcement to minimize irregularities in the context of prosecuting traffic violations. Ditlantas Polda Central Java made a breakthrough in the form of ETLE Mobile National Precision, which is a method of prosecuting violations using cellphones implemented in all ranks of the Central Java Regional Police. Klaten Police, based on 2020 data, is ranked 4th in terms of traffic accidents, the use of ETLE in prosecuting traffic violations is expected to be a solution, but until the end of 2023, the number of traffic violations and accidents is still increasing. This research uses a qualitative approach. The research focus in this study is Optimizing the Enforcement of Traffic Violations through the Precision National Mobile ETLE Application by the Klaten Police Traffic Unit to Realize Equitable Law Enforcement. In data validity, researchers use data triangulation. For data analysis techniques using data reduction, data presentation and conclusion drawing.Hasll from this study are still many findings of the implementation of traffic violations by Satlantas Polres. The obstacles include the lack of personnel, lack of planning, inadequate budget, absence of detailed implementation guidelines, and lack of socialization. Based on the results of this research, researchers have several kinds of problem solving. The problem solving that can be done is to apply a priority scale by utilizing the existing number of personnel and budget, improving the activity plan, making a temporary implementation guidebook, and conducting socialization through various media platforms.